Safeguarding Physician Wellbeing Using Checklists for Personal, Professional, and Psychological Safety. - Wei, Julie L. (Milton : Productivity Press, 2024)
The United States is facing a worsening epidemic of physician burnout with unprecedented numbers of them leaving the workforce and practice of clinical medicine across all career stages. The prevalence of physician burnout has accelerated through COVID-19, resulting in an anticipated serious national shortage of physicians within the current decade amidst an increased proportion of aging and unhealthy population. The critical shortage of physicians coupled with an unhealthy physician workforce results in longer wait times for access, continued increased healthcare costs, decreased quality of care, and worsening patient experience. Despite increasing media coverage, published data, and identification of system-based factors that erode physician wellbeing, no standardized systematic solution has been implemented across hospitals, health systems, or a variety of employment models or practice settings for any or all doctors regardless of whether they are primary care, medical, or surgical subspecialists. Effective solutions to mitigate physician burnout, protect current working physicians, and keep them from leaving medicine require a SHIFT and a more individualized approach. Many proposed academic models address system-based factors, but such solutions depend greatly on those who employ doctors. Executive leadership in charge of healthcare systems are often challenged by physician burnout and their desired autonomy, against the need for standardization of care delivery to improve quality and decrease cost. Physician productivity measures continue to be based on data samples of physician compensation surveys supplied by companies like Sullivan Cotter or Medical Group Management Association (MGMA). Such benchmarks are commonly used but data may not reflect specific realities for any organizations nor the rapid changes in the landscape of US healthcare amidst mergers, acquisitions, consolidation, and shifts in employment models from insurance and online retail giants and private equity. This book uses a "checklist" approach to empower any medical student, resident, fellow, or practicing physician to create and experience psychological, personal, and professional safety and wellbeing. Not only can individual physicians choose and use these checklists themselves, but those who live with, love, and cherish one or more physicians in their families and/or lives can use this book to understand physician realities and their risks.
Chapter 3 -- Additional Resources -- Chapter 5 -- Chapter 6 -- Chapter 7 -- Chapter 11 -- Additional Citations -- Chapter 12 -- Chapter 13 -- Chapter 14 -- Index
Description based upon print version of record.
Keywords: Physicians -- Psychology; Burn out (Psychology); MEDICAL / Physicians; MEDICAL / Mental Health